1997
DOI: 10.1097/00001610-199707000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric Tube Feeding and Medication Administration: A Survey of Nursing Practices

Abstract: Using a 62-item, investigator-developed mailed questionnaire, this descriptive study of 350 randomly selected staff nurses sought to identify variations in practices in the care of patients with nasogastric tubes (NGT). Reported here are the results from the 35 questionnaire items related to NGT feedings and medication administration. Wide variations were found in the amount of gastric residual considered "excessive," as well as in whether the entire residual was returned to the stomach. A large percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For critically ill patients who cannot consume or have an oral diet, finding ways to administer drugs through the enteral feeding tube presents a challenge. Although administration of medication via enteral tube is specifically a nursing responsibility, they had limited baseline knowledge about pharmaceutical form, drug dosage, or interaction 4,5,10,14…”
Section: Discussionmentioning
confidence: 99%
“…For critically ill patients who cannot consume or have an oral diet, finding ways to administer drugs through the enteral feeding tube presents a challenge. Although administration of medication via enteral tube is specifically a nursing responsibility, they had limited baseline knowledge about pharmaceutical form, drug dosage, or interaction 4,5,10,14…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 219 ICU nurses at a university medical center found that 90 (50%) of 180 respondents considered volumes exceeding 100 ml excessive, 24 but wide variation exists regarding the actual volume considered excessive and the amount returned to the stomach. 25 Current recommendations include evaluating the patient's abdomen for tenderness and bowel sounds and assessing gastric residual volumes every 4-12 hours. 5,8,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Most clinicians recommend temporarily stopping intragastric EN if residual volume exceeds 100-150 ml and resuming it when the volume declines below 50-75 ml.…”
Section: Clinical Interpretationmentioning
confidence: 99%
“…41 Based on general practice, it is reasonable to assess aspirated gastric residual volumes every 4-12 hours and interpret intolerance as a single volume of 150-200 ml or two consecutive volumes exceeding 100-120 ml. 8,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] A tender abdomen or the presence of hypoactive or absent bowel sounds may aid the assessment of intolerance, but lack of bowel sounds should not contraindicate intragastric EN. The residual volume that may be safely reintroduced has not been studied, but volumes of 50-200 ml are considered appropriate.…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Case reports and observational studies of enteral medication error, as well as multiple surveys, have documented inappropriate drug preparation and administration practices. Although >90% of survey respondents are confident in the appropriateness and effectiveness of their method for enteral drug preparation and administration, as many as 1–3 inappropriate techniques have been identified per respondent 67–73 …”
Section: Enteral Drug‐use Processmentioning
confidence: 99%